The Existentialism Philosophy (Jean-Paul Sartre and Søren Kierkegaard) in the Contextualization of Education in the Digital Era - Afryansyah Afryansyah; Ismail Sukardi; Mardiah Astuti; Andre Bahrudin (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
This study examines the contextualization of existentialist philosophy—rooted in the thoughts of Jean-Paul Sartre and Søren Kierkegaard—within the framework of education in the digital era. The study employs a qualitative literature review approach, analyzing reputable journals and philosophical texts to explore existentialist concepts and their integration into contemporary education. The research reveals that existentialist principles, such as freedom, responsibility, and the search for meaning, align with the characteristics of digitalization in education, particularly in fostering autonomy and self-awareness among learners. It also highlights the role of educators in mediating the application of existentialism to ensure a balance between the positive and negative impacts of digital freedom. The findings emphasize that digital tools can enhance educational practices by encouraging critical thinking, individuality, and ethical responsibility, resonating with existentialist ideals. However, challenges remain in addressing potential individualism and misuse of digital platforms. The study concludes that the adaptation of existentialist philosophy offers valuable insights for navigating the transformative landscape of digital education while promoting holistic personal development.